Phosphorus and Oxygen Dual‐Doped Porous Carbon Spheres with Enhanced Reaction Kinetics as Anode Materials for High‐Performance Potassium‐Ion Hybrid Capacitors - Zhao, Shuoqing; Yan, Kang; Liang, Jiayu; Yuan, Qinghong; Zhang, Jinqiang; Sun, Bing; Munroe, Paul; Wang, Guoxiu (Advanced functional materials, 2021)
Hard carbons with low cost and high specific capacity hold great potential as anode materials for potassium‐based energy storage. However, their sluggish reaction kinetics and inevitable volume expansion degrade their electrochemical performance. Through rational nanostructure design and a heteroatom doping strategy, herein, the synthesis of phosphorus/oxygen dual‐doped porous carbon spheres is reported, which possess expanded interlayer distances, abundant redox active sites, and oxygen‐rich defects. The as‐developed battery‐type anode material shows high discharge capacity (401 mAh g−1 at 0.1 A g−1), outstanding rate capability, and ultralong cycling stability (89.8% after 10 000 cycles). In situ Raman spectroscopy and density functional theory calculations further confirm that the formation of PC and PO/POH bonds not only improves structural stability, but also contributes to a rapid surface‐controlled potassium adsorption process. As a proof of concept, a potassium‐ion hybrid capacitor is assembled by a dual‐doped porous carbon sphere anode and an activated carbon cathode. It shows superior electrochemical performance, which opens a new avenue to innovative potassium‐based energy storage technology. Phosphorus/oxygen dual‐doped porous carbon spheres with expanded interlayer distances and abundant active sites are synthesized through a chemical vapor deposition process. The obtained anode materials show exceptional potassium storage capability and outstanding structural stability, which suggests their huge potential as anodes for high‐performance potassium‐ion hybrid capacitors.